Artemis Fowl and the lost colony - Colfer, Eoin. (London : Puffin Books, 2011)
Teenager Artemis Fowl solves a temporal equation that helps him and Captain Holly Short track fairy demons who are appearing from another dimension, but there is another person who has figured out the formula and abducts one of the beings.
5.3
5-8.
5-8
Keywords: Fairies -- Juvenile fiction; Magic -- Juvenile fiction; Fairies -- Fiction; Fantasy; Magic -- Fiction; Fairies -- Fiction; Magic -- Fiction; England -- Juvenile fiction; England -- Fiction; England -- Fiction; Fantastic fiction; Fantastic fiction